Time is knowledge: What response times reveal - Jean-Michel Benkert; Shuo Liu; Nick Netzer (University of Zurich, Department of Economics, 2024)
Response times contain information about economically relevant but unobserved variables like willingness to pay, preference intensity, quality, or happiness. Here, we provide a general characterization of the properties of latent variables that can be detected using response time data. Our characterization generalizes various results in the literature, helps to solve identification problems of binary response models, and paves the way for many new applications. We apply the result to test the hypothesis that marginal happiness is decreasing in income, a principle that is commonly accepted but so far not established empirically.
Keywords: C14; D60; D91; I31; 330; response times; chronometric effect; binary response model; non-parametric identification; decreasing marginal happiness